Food safety management in china: a perspective from food quality control system - Zhou, Jiehong; Jin, Shaosheng (World Scientific Publishing Co. Pte. Ltd, 2013)
In recent years, China has taken a number of effective measures to strengthen the supervision of food quality and safety, but food safety incidents still occur sometimes. The recurrence and intractability of such incidents suggest that, in addition to the imperfect supervision system, the greatest obstacle to China's food quality safety management is that China's “farm to fork” food supply chain has too many stages, the members on the supply chain have not form a stable strategic and cooperative relation, and on the other hand, during the transitional period, some practitioners lack social responsibility. Therefore, China's food quality safety management and the establishment of food quality and safety traceability system should follow the development trend of international food quality and safety supervision, and should combine with the establishment of China's agricultural industrialization and standardization, integrate China's existing but isolated effective measures, such as the establishment of bases for the implementation of the system of claiming certificates or invoices, for the performance of Management Regulations for Pig Slaughtering and Quarantine Inspection in Designated Places, and for the conduct of World Expo, as well as the establishment of market access system, take into consideration the demand, the dynamic mechanism, and the performance of important measures of food supply chain members for food quality and safety control, as well as the difficulties and the deep-seated reasons in the implementation process of such measures.